Restorative vs. Pathogenic Public Spaces: Investigating the Impact of Urban Green-Space Parks in Rapidly Growing Mid-Sized Cities (EAAE Joint Publishings, 2026)
Urban green spaces play a critical role in shaping mental health, offering environments that can either restore well-being or exacerbate stress. However, access to these restorative benefits often reflects deeper socio- economic patterns, raising questions about equity and inclusion. This study investigates how visitor perceptions of urban parks—gathered through Google reviews—differ between neighborhoods with varying degrees of gentrification. Examining this data alongside the socio-economic trajectories of neighborhoods in mid-sized cities like Greenville, Spartanburg, and Charlotte aims to inform urban planning and policy-making strategies that prioritize equitable access to restorative green spaces, ultimately ensuring that parks benefit all community members.The stakes of this inquiry are significant. As cities grow and invest in public green spaces, disparities in access and perceptions of safety, usability, and comfort can emerge and perpetuate social inequities. This study situates itself at the intersection of urban design, public health, and social justice, asking: How do perceptions of parks as restorative or pathogenic align with neighborhood socioeconomic profiles, particularly in areas experiencing gentrification compared to historically marginalized neighborhoods?By analyzing user-generated reviews, this paper uncovers recurring themes related to greenery, safety, accessibility, and community-oriented design. These findings are then juxtaposed with neighborhood-level data to reveal patterns of preference. Readers will learn how urban greening efforts may unintentionally contribute to social stratification and strategies for designing parks that prioritize inclusivity and shared well-being. Ultimately, this research highlights the need to reimagine green spaces as equitable resources, ensuring their benefits are accessible to all, regardless of socioeconomic status or neighborhood context.